(untitled) (Semiárida, 2020)
The agricultural cooperative movement in Argentina has experienced changes that need to be analyzed from cultural interpretations of relationships and social life of the cooperative members in their cooperatives. This paper explores the meanings and practices that are built on cooperatives. The construction of these objects of study is done on the basis of how articulate the conditions of existence of cooperatives and the discourse of the members producers on them. It appears that in general the members of agricultural cooperatives producing scholars argue that the cooperative promotes cooperative values, however the senses that give are different. Mostly partners with profitable agrarian structure itself and imagine a cooperative with differentiated service and corporate look, an image difficult to imagine from the cooperative principies because the emphasis is on the partner and not in the cooperative. For its part, the partners own no land and cost structure as a result of competition that consider experience, imagine the cooperative as a business enterprise, an image that emphasizes the cooperative, a cooperative must seduce the partner. This leaves the cooperative identity narrative which holds that builds cooperative partner rather than the reverse.